Do you what I say? People reconstruct the syntax of anomalous utterances. Issue 2 (7th February 2017) - Ivanova, Iva; Branigan, Holly P.; McLean, Janet F.; Costa, Albert; Pickering, Martin J.
ABSTRACT: We frequently experience and successfully process anomalous utterances. Here we examine whether people do this by "correcting" syntactic anomalies to yield well-formed representations. In two structural priming experiments, participants' syntactic choices in picture description were influenced as strongly by previously comprehended anomalous (missing-verb) prime sentences as by well-formed prime sentences. Our results suggest that comprehenders can reconstruct the constituent structure of anomalous utterances – even when such utterances lack a major structural component such as the verb. These results also imply that structural alignment in dialogue is unaffected if one interlocutor produces anomalous utterances.